SMALL, MEDIUM, MICRO ENTERPRISES, AND FINANCIAL GROWTH CYCLE - Elok Pakaryaningsih (Universitas Hayam Wuruk Perbanas, 2011)
Research on small, medium, and micro-sized enterprises (SMMEs) is considered interesting.This study attempts to examine the existence of external financing on micro, small and mediumenterprises in Jogjakarta, especially to support the existence of The Financial GrowthCycle Model proposed by Bergel and Udell (1998). This model argues that, as the enterprisesgetting mature in terms of age, size and published information, the external financings aregradually employed. Besides that, this study also examines the policy implication regardingthe existence of Financial Growth Cycle Model. Using multinomial logistics regression, 100of micro, small, and medium sized-enterprises in Jogjakarta are analyzed. The result showsthat micro, small and medium-sized enterprises in Jogjakarta have a high tendency to useinternal financings rather than external ones. This evidence is due to the major characteristicsof the sample, which they are considered under developed or immature. Moreover, theresults suggest that the Financial Growth Cycle Model is supported. The result also suggeststhat microfinance institution should follow three strategies to provide source of capital.Those strategies are market segmentation, loan portfolio, and assisting program for SMMEs.